Exporting behavior and the demand for skills in German establishments - Arnd Kölling; Antje Mertens (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2020)
The analysis deals with the influence of exporting on the demand for workers with different skill levels. Previous literature suggests that this includes two major topics. First, productivity of exporting firms may increase due to learning facts after entering international markets and/or be higher initially due to selfselection of firms into exporting. Second, exporting potentially leads to a change in the employment structure towards highly skilled workers. We applied a conditional difference-in-difference regression model of labor demand for three different skill levels to investigate this hypothesis. For this purpose, we use German establishment panel data that covers the period from 2000 to 2014. The outcome shows that not only self-selection into exports must be controlled for but also that changes in employment seem to be skill biased in manufacturing firms starting export activities. Nevertheless, there are no corresponding findings for firms that stop exporting or establishments in the service sector respectively.
Keywords: F14; J23; J24; C31; 330; Export; labor demand; skills; treatment model